Cultural Diversity and Islam - Mucahit Bilici (International Institute of Islamic Thought, 2004)
As a compilation of papers presented at an international conference (1998) on “Cultural Diversity and Islam” at American University in Washington, DC, this volume brings together the contributions of a wide array of scholars. It has four sections and twelve chapters dealing with diversity and/or pluralism in relation to Islam. The first section, “Cultural Diversity in Civilizational Perspective,” provides a macro (and at times comparative) perspective on Islam and diversity. In chapter 1, the editors prepare the ground for discussion by providing some definitions, potential questions, and chapter summaries. They also explain why they prefer the concept of diversity over pluralism. In chapter 2, Seyyed Hossein Nasr discusses what he calls “a theoretical and practical dilemma” in Islam: unity vs. diversity. Entitled “Unity and Diversity in Islam and Islamic Civilization,” this chapter makes general statements about the nature of diversity in Islam and how unity and uniformity differ. Nasr argues that “Islam’s refusal to reduce this unity-in-diversity to mere uniformity, far from weakening the faith, has been a major cause of its strength through the ages” (p. 33). To understand more fully how Islam created a unitary civilization that has thrived on diversity, he looks at different cultural zones within Islam. The issue of Islam and diversity is often discussed in reference to the assertion of Islam’s compatibility with democracy as well as the challenges produced by globalization, which brought Islam into closer contact with western and other cultures. It is uncommon for scholars addressing such issues to raise the question of power. Sulayman S. Nyang’s excellent article in chapter 3 brings the issue of power into the equation. Looking at what he calls the factors and ...